The rediscovery of Rungia hirpex (Acanthaceae) in Yunnan, China - Lin, Zhe-Li; Xu, Chao; Deng, Yun-Fei (Phytotaxa, 2016)
The rediscovery of Rungia hirpex (Acanthaceae) is reported from Yanjin and Daguan, Yunnan, China about 100 years after the type collection made by E. E. Maire between 1905 and 1916. A revised description of the species including its pollen and seed morphology and chromosome number is provided. The lectotype is designated and the conservation status is assessed. In addition, a color plate, line drawing and distribution map are provided.